Discharge Hemoglobin Association with Long-Term Outcomes of ST-Elevation Myocardial Infarction Patients Undergoing Primary Percutaneous Coronary Intervention - Ming Gao; Xinying Zhang; Ling Qin; Yang Zheng; Zhiguo Zhang; Qian Tong; Hang Li (Cardiovascular Therapeutics)
Background. Anemia following acute myocardial infarction (AMI) is associated with poor outcomes. While previous studies in patients with AMI have focused on anemia at admission, we hypothesized that hemoglobin (Hb) decline during hospitalization and lower discharge Hb would be associated with greater long-term mortality in patients undergoing primary percutaneous coronary intervention (PCI) for ST-segment elevation myocardial infarction (STEMI). Methods. We analyzed records of 983 STEMI patients who were treated with primary PCI. The primary end point was all-cause mortality at 1 year and 2 years. The relationship between discharge Hb levels, decline in Hb levels, bleeding event classification, and all-cause mortality was determined. Results. Overall, 16.4% of patients had bleeding events, which were classified by the Thrombolysis in Myocardial Infarction (TIMI) score as 7% minimal, 8.6% minor, and 0.9% major. No significant gastrointestinal bleed and cerebral hemorrhage occurred in hospitals among these patients. The incidence rate of the 2-year all-cause mortality increased with severity of the bleeding event score (8.78% for no bleeding vs. 11.59% for minimal bleeding vs. 20.24% for minor bleeding vs. 55.56% for major bleeding, P<0.001). Discharge Hb was significantly associated with 2-year mortality in an unadjusted model (hazard ratio (HR) per 1 g/L decrease in discharge Hb = 1.020, 95% confidence interval (CI): 1.006–1.034, P=0.004) and in a confounder-adjusted model (HR per 1 g/L decrease in discharge Hb = 1.024, 95% CI: 1.011–1.037, P<0.001). The odds ratio (OR) for all-cause mortality at 2 years for participants with Hb below the twentieth percentile was 3.529 (95% CI: 1.976–6.302) and 2.968 (95% CI: 1.614–5.456) after adjustment for age and gender and 2.485 (95% CI: 1.310–4.715) after adjustment for all covariates. Conclusions. In this population of patients hospitalized for STEMI, all-cause mortality increased with lower discharge Hb, and discharge Hb was a significant predictor of mortality risk.